SBM ITB 2017 BATCH STUDENTS PREFERENCES ON SECOND ACCOUNT INSTAGRAM CONTENT: APPLICATION OF CONJOINT ANALYSIS - Luddin, M Ilham; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. Instagram has become the third most used social media, it now have an amount of 700M user on April 2017. Nowadays, there are countless fashion brands that is using Instagram as one of their platform to gain sells, gain awareness, gaining engagement, etc. There are now 500 million members of the Instagram community and Instagrammers interested in fashion (Instagram data, 2016). In Indonesia, there are many cases with local fashion brand that maintain an aesthetic feeds for their main Instagram account, so many of them come up to a solution by creating a 2nd account, many of them creates 2nd account as their digital catalogue or digital look book of their product. The problem is that there are no basic guideline on creating the 2nd account content that based on the consumer preferences when browsing to look the information they needed. By making an efficient and effective content based on the consumer needs of information to keep the user engagement similar with the brands main account. This research is expected to measure what are the content combination information that the consumer needs with the conjoint analysis. This analysis will use two method which is the qualitative analysis by interview the targeted respondent and the quantitative analysis by using the conjoint analysis method with online and offline questionnaire but will be more focused on the both result of the online and offline.Keywords: Marketing Research, Instagram, Instagram Second Account, Conjoint Analysis, Social Media.